Karakteristik Dan Pergerakan Sebaran Penderita DBD Berdasarkan Geographic Information System Sebagai Bagian Sistem Informasi Surveilans di Kecamatan Karawang Barat Kabupaten Karawang Provinsi Jawa Barat - Doni Lasut (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. West Karawang is a part of Karawang District that have high case incidence in three years later. This research uses cross sectional study method was conducted that aimed to gain information of mapping DHF endemic region use GIS (Geographic Information sys-tems) as a part of surveillance informatics system 2008. The special goals are to know the spatial aspect of the movement pattern , socio-demographic, larvae index, vector control programs, land systems and precipitation. The results of study are movement pattern of DHF in West Karawang is local, the socio-demographic of sex and marital status there are no special different, group of class age 15 – 44 years old (53,70%), non-formal working (81,48%) is the highest. The socio-demographic of education Senior High School (38,89%) is the highest too. Almost of The housing type permanent (94,44%) is the dominant and the average wide building 50-100 meters (66,67%) is the highest. House index larvae is 55,10% and container larvae index is 15,51%. The vector control program of fogging in study area 70,37% is done and PSN program activity (81,48%) this fact shown that there are many possibility for breeding place in this district. The Use of GIS helps to handle huge of data easily and much more information can be display clearly.